2021
DOI: 10.1021/acs.iecr.0c06344
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effective Diffusion Coefficient and Filtration Performance of Micro/Nanofibrous Composite Layered Filters

Abstract: Diffusion is an important filtration mechanism of fibrous filters for removing fine particles from gas streams. An analytical model is proposed in this work, based on fractal theory, to quantify the effective diffusion coefficient (EDC) across micro/nanofibrous filters with a layered structure. To show the influence of macroscopic parameters of fibrous filters on EDC, the present models are expressed in terms of fiber diameter. Polyacrylonitrile (PAN) nanofibers were prepared by electrospinning on melt-blown p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…The viscous resistance increased because of the increase of fiber surface area contacted by air flow, resulting in a higher pressure drop. 12,36 A number of previous studies had focused on the effect of fiber orientation and porosity on the pressure drop. 22,24−29 The comparison of the experimental and simulation results with the prediction model results proposed by Davies, 24 Happel, 25 Spielman and Goren, 26 Drummond, 27 Tomadakis and Robertson, 28 Yang, 29 and Woudberg 22,37 is plotted in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscous resistance increased because of the increase of fiber surface area contacted by air flow, resulting in a higher pressure drop. 12,36 A number of previous studies had focused on the effect of fiber orientation and porosity on the pressure drop. 22,24−29 The comparison of the experimental and simulation results with the prediction model results proposed by Davies, 24 Happel, 25 Spielman and Goren, 26 Drummond, 27 Tomadakis and Robertson, 28 Yang, 29 and Woudberg 22,37 is plotted in Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…The lamination process caused the gap between the fibers to become smaller, and it could be seen that the tortuosity of the streamlines after lamination was significantly greater than before lamination. The viscous resistance increased because of the increase of fiber surface area contacted by air flow, resulting in a higher pressure drop. , …”
Section: Resultsmentioning
confidence: 99%
“…35 In the numerical study, the straight fiber is also commonly used to generate a virtual filter model and assess filter performance, compared to curved fiber. 25,28 Soltani et al conducted a numerical study to compare the permeability of curved and straight fibers. The curved fiber was obtained from X-ray μCT, while the straight fiber was developed by a MATLAB-based program from morphological analysis of X-ray μCT.…”
Section: Artificial Filter Domainsmentioning
confidence: 99%
“…Several researchers have modeled fibrous media using Cartesian grids to reduce computational costs. Bai et al 25 and Maddideni et al 26 reconstructed the 3D fiber structure of an actual filter using the commercial solver GeoDict software based on the voxel method. Pradhan et al 27 used the same voxel method and developed an artificial 3D model of a fibrous filter.…”
Section: Introductionmentioning
confidence: 99%
“…As a first step, a virtual model is created by reflecting the actual material characteristics, either by reconstructing a resolved model from an actual sample analyzed by X-ray computed tomography (Xμ-CT) or by generating a digital model (unresolved model) with key input parameters such as fiber diameter, porosity, density, and thickness. , Validation of a virtual model can be attained by comparing the characteristics of virtual and actual materials; thus, physical experiments are accompanied to verify the simulation process. , An earlier study by Pan et al reported that a reconstructed filter model (resolved model) exhibited a better fit with the experimental data than a digital model. The main focus of the simulation study has been in understanding the particle behavior in the air flow and optimizing the structural design of filter materials. In other cases, the simulation was conducted on filter media to predict the initial resistance and efficiency at specific test conditions. , However, in most simulation cases, the time factor has been hardly considered, whereas the filtration characteristic with a timeframe may be important for a comprehensive understanding of filtration behavior in practical scenarios.…”
Section: Introductionmentioning
confidence: 99%